Wingardium Leviosa Wand / Sharifah Nur Atiqah Wan Akil - Wan Akil, Sharifah Nur Atiqah (2020)
Wingardium Leviosa wand is a magical wand which is a new product idea which create from a common problem that society having to deal in their daily life nowadays. This report will provide a detailed road map on how to convert the ideas and vision into real, functioning, profitable and viable product. Today, the world is grappling with an invisible, deadly enemy, which can kill human being in just a blink of eyes. The existence of shocking smallest creature in universe which is coronavirus (Covid-19) has electrifying the worldwide. As the coronavirus pandemic has stretched around the world, it time to contribute our sweat, tears and blood to produce products that is useful to be use in this critical time. Wingardium Leviosa Wand is a unique product that made up of aluminium which is known to be one of eco- friendly materials. This product is focusing on giving communities a fresh, new, healthy and a better life by protecting people from harmful, dangerous and an invisible creature such as bacteria and viruses. Other than that, this wand also acts as strong shield to the consumer, that no single microorganisms able to pass through them.